Mechanical Biomimetic Nanocomposites for Multidimensional Treatment of Arterial Thrombosis - Ying Li; Qi Xiang; Yan Zhang; Fuxue Luo; Yunfang Wu; Haitao Ran; Yang Cao (Advanced Science)
Abstract Arterial thrombosis is a severe cardiovascular condition associated with high mortality and disability rates. Traditional pharmacological thrombolytic therapies, however, are limited by a narrow therapeutic window, short drug half‐lives, restricted therapeutic effectiveness, and the risk of hemorrhagic complications. Moreover, the unique biological microenvironment of arterial thrombosis is characterized by high shear stress and an inflammatory milieu rich in reactive oxygen species (ROS), resulting in a relatively high recurrence rate. To address these challenges, a mechanical biomimetic nanocomposite MPB‐NO‐UK@PM is developed by doping sodium nitroprusside, a nitric oxide (NO) donor, into mesoporous Prussian blue (MPB) nanoparticles to form MPB‐NO, which is then loaded with urokinase (UK) and coated with platelet membranes (PM). The nanocomposite exhibits excellent thrombus‐targeting ability and enhances thrombolytic efficacy through synergistic photothermal and pharmacological, while simultaneously reducing the risk of bleeding. The released NO induces antiplatelet aggregation effects, while Prussian blue effectively scavenges ROS and inflammatory cytokines, thereby preventing thrombus recurrence. Additionally, the nanocomposite possesses superior photoacoustic imaging capabilities, enabling visualization of thrombus diagnosis and treatment. This therapeutic approach represents a novel pathway for the multidimensional and efficient management of arterial thrombosis.